Formation of secondary organic aerosols from the ozonolysis of dihydrofurans - Diaz de Mera, Yolanda (2017)
In this work we report the study of the ozonolysis of 2,5-dihydrofuran and 2,3-dihydrofuran and the reaction conditions leading to the formation of secondary organic aerosols. The reactions have been carried out in a Teflon chamber filled with synthetic air mixtures at atmospheric pressure and room temperature. The ozonolysis only produced particles in the presence of SO2. Rising relative humidity from 0 to 40% had no effect on the production of secondary organic aerosol in the case of 2,5-dihydrofuran, while it reduced the particle number and particle mass concentrations from the 2,3-dihydrofuran ozonolysis. The water-to-SO2 rate constant ratio for the 2,3-dihydrofuran Criegee intermediate was derived from the secondary organic aerosol (SOA) yields in experiments with different relative humidity values, kH2O/kSO2 = (9.8 ± 3.7) × 10-5. The experimental results show that SO3 may not be the only intermediate involved in the formation or growth of new particles in contrast to the data reported for other Criegee intermediate-SO2 reactions. For the studied reactions, SO2 concentrations remained constant during the experiments, behaving as a catalyst in the production of condensable products. Computational calculations also show that the stabilised Criegee intermediates from the ozonolysis reaction of both 2,5-dihydrofuran and 2,3-dihydrofuran may react with SO2, resulting in the regeneration of SO2 and the formation of low-volatility organic acids.